Advanced 3D failure characterization in multi-layered PCBs. (December 2016) - Grünwald, E.; Hammer, R.; Rosc, J.; Maier, G.A.; Bärnthaler, M.; Cordill, M.J.; Brand, S.; Nuster, R.; Krivec, T.; Brunner, R.
Abstract: The non-destructive inspection of printed circuit boards (PCBs) represents an issue of constant importance in microelectronics. In this study, the detection of delaminations in modern PCBs by scanning acoustic microscopy (SAM) is described. It is shown that, even though the acoustic analysis is complicated due to the multi-layered build-up, delamination/delaminations can be located within the PCB by (1) utilizing the resulting curvatures of the layers for the detection, (2) analysing the generated SAM 2D data in combination with novel 3D data and (3) using Elastic Finite Integration Technique (EFIT) based simulations. Complementary destructive physical cross-sectioning corroborates the obtained results. Highlights: Indirect delamination detection for PCBs via SAM is presented. Curvatures of PCB-layers are used for delamination detection. 3D visualizations of the delaminated PCB from SAM data are acquired. Purpose-designed simulations are carried out and support the SAM findings. Destructive physical cross-sectioning corroborates the obtained results.